2019
DOI: 10.1001/jamapediatrics.2019.0081
|View full text |Cite
|
Sign up to set email alerts
|

Survival Trends in Infants Undergoing Allogeneic Hematopoietic Cell Transplant

Abstract: IMPORTANCE Studies demonstrating improved survival after allogeneic hematopoietic cell transplant generally exclude infants.OBJECTIVE To analyze overall survival trends and other outcomes among infants who undergo allogeneic hematopoietic cell transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…6 Despite these achievements, mortality following pediatric HCT remains significant, and efforts to identify novel risk factors for inferior outcomes are essential. 7 Social determinants of health, including poverty, are widely recognized as major contributors to both adult and pediatric health outcomes in the United States. [8][9][10] While studies in both pediatric oncology [11][12][13][14] and adult HCT [15][16][17] indicate that socioeconomic status is an independent predictor of inferior survival outcomes, including both relapse and overall survival, limited data exist exploring the pertinence of socioeconomic status in pediatric HCT.…”
Section: Introductionmentioning
confidence: 99%
“…6 Despite these achievements, mortality following pediatric HCT remains significant, and efforts to identify novel risk factors for inferior outcomes are essential. 7 Social determinants of health, including poverty, are widely recognized as major contributors to both adult and pediatric health outcomes in the United States. [8][9][10] While studies in both pediatric oncology [11][12][13][14] and adult HCT [15][16][17] indicate that socioeconomic status is an independent predictor of inferior survival outcomes, including both relapse and overall survival, limited data exist exploring the pertinence of socioeconomic status in pediatric HCT.…”
Section: Introductionmentioning
confidence: 99%
“…In 472 infants transplanted for malignant diseases in 2000–2014 and reported to the Centre for International Blood and Marrow Transplant Research (CIBMTR), 182 of whom had ALL, Parikh et al observed no improvement in the outcome measures over time, as opposed to the general improvement of transplant results for most other ages and disease groups over time. Both the rate of relapse and the rate of toxicity remained high, with a high incidence of sinusoidal obstruction syndrome (SOS) ( 18 ). These data illustrate the challenges in infant ALL with high risks of both toxicity and relapse.…”
Section: Conventional Strategies Including Haematopoietic Stem Cell T...mentioning
confidence: 99%
“…A study conducted by Tracey et al, including patients with ALL aged ≤18 years old, concluded that neither a TBI dose in excess of 13 Gy nor the addition of etoposide to cyclophosphamide could improve OS after HSCT but did increase TRM ( 18 ). TRM, as expected, was generally higher in patients >10 years old compared to in patients <10 years old ( 21 ).…”
Section: Conventional Strategies Including Haematopoietic Stem Cell T...mentioning
confidence: 99%
“…Despite the survival of both children reported by Martinez et al, there is an expected mortality at least 10% for children with severe immune disorders undergoing HSCT. 7 Moreover, both children in this study developed both acute and chronic graft-versus-host disease (GVHD), which was fortunately highly responsive to steroids, but with any allogeneic HSCT performed for a chronic nonmalignant condition, there is the possibility of exchanging 1 chronic disorder for another (ie, chronic GVHD). As the authors point out, the risk of GVHD might be reduced by interferon blockade during the acute phase of transplantation.…”
Section: Stella M Davies | Cincinnati Children's Hospital Medical Centermentioning
confidence: 93%